Empire of Direct Mail : How Conservative Marketing Persuaded Voters and Transformed the Grassroots - Moriyama, Takahito (Book collections on Project MUSE., 2022)
"The rapid growth of the conservative movement has long fascinated historians, many of whom have focused on the grassroots efforts in the Sunbelt. Takahito Moriyama examines how conservative operatives got their message out to their supporters through computerized direct mail, a significant but understudied communication technology. The story centers on Richard Viguerie, a pioneer of political direct mail who was known as the "Funding Father" of the conservative movement. His consulting firm established a database of conservative prospects and sent millions of letters. By the 1970s, Viguerie emerged as the central fundraiser in conservative politics, financing right-wing organizations and politicians, such as George Wallace, Jesse Helms, and Ronald Reagan. Moriyama shows that the rise of right-wing direct mail communication in the postwar years coincided with a new strategy: the use of this new technology to stoke negative emotions, such as fury and fear, among the letter recipients. Conservative operatives learned that playing on these emotions was the best way to persuade individuals to take action. Before talk radio, Fox News, Twitter, and Cambridge Analytica, conservatives used direct mail to spread messages of anxiety and anger to raise funds and mobilize the grassroots. Through extensive archival research of fundraising activities in the conservative movement and key elections from 1950 to 1980, Empire of Direct Mail offers a political history of the role of communication technology in the development of modern conservatism in the United States"--